Rationalization of Raw Materials and Fuel and Energy Base of the Construction Industry of Kazakhstan Industrial Regions - DONTSOV, Sergey Semyonovich; SARTOVA, Rysty Bozmanaevna; AIGUZHINOVA, Dinara Zeinullaevna; ZHANAT, Myrzabek; KADYROVA, Akmaral Satbekovna (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The article deals with an actual problem - the rationalization of raw materials and fuel and energy base of the construction industry of Kazakhstan industrial regions. It covers the basic principles of rational use of natural resources and the comprehensive processing of mineral raw materials as elements of the state strategy, as well as statistics on investments aimed at environmental protection, sustainable use of natural resources of Kazakhstan and the relevant costs by types of environmental activities. The article sets forth the theoretical basis and practical recommendations on the effective organization of the raw material base of the construction industry as the most material intensive industry capable of utilizing the largest volumes of industrial waste as the main raw material and additives for the production of building materials. A number of examples of successful use of large-tonnage industrial waste instead of the traditional raw materials ensuring environmental, economic, organizational and technological effects were provided. The measures for environmental protection and rational use of natural resources in the construction industry were recommended. The conditions for rational organization of the fuel and energy base of the construction industry, involving selection of the most efficient types of fuel, energy sources used in the construction production, as well as the most efficient schemes for providing energy resources to production processes, taking into account energy saving, were provided.